Предмет: Алгебра, автор: vova710

Упростить (2x+3)^-(2x-1)^=

Ответы

Автор ответа: iriska124
0
1)2x2+12х+9 - (4х2-4х+1) =2х2+12х+9-4х2+4х-1=-2х2+16х+8 =-2*(х2-8х-4)
2)(3a-b)(a+b)+(b-3a)=3а²-ба-б²+3аб+б-3а=3а²-б²-3а-2аб+б 
3)(3a-b)(a+b)+(b-3a)(b+3)=3а²-аб-б²+3аб+б²-3аб+3б-9а = 3а²-аб+3б-9а =(3а²-9а)-(аб-3б) =3а*(а-3)-б*(а-3) =(а-3)*(3а-б)
Автор ответа: iriska124
0
Да
Автор ответа: vova710
0
Реши)Упростить (3a-b)(a+b)+(b-3a)(b+3)=
Автор ответа: lidusya13
0
=(2x+3-2x+1)(2x+3+2x-1)=(x+4)(5x+2)
Если упростить , можно перемножить:
5х^2+22х+8
Похожие вопросы